SISTEM FUZZY INFERENSI UNTUK CUSTOMISE FAN PADA SISTEM RUMAH CERDAS - Andi Farmadi; Dwi Kartini Kartini; Muliadi Muliadi (Lambung Mangkurat University, 2020)
AbstractSmart machine-based home development is becoming the current trend because the system can be controlled intelligently by machines. The air conditioning system without the use of air conditioning requires a type of fan to stabilize the temperature and humidity outside the house and inside the house using a blower fan or also called an exhaust fan, but this fan is only limited to circulating air circulation between the outside air and inside the house so that the tendency for the inside air adjust to the outside air, to control the air according to the user it will be manually customized by the user. And for fans in the home room a fan is used which blows air around the fan in circulation. The application of the fuzzy system can provide a fan rotation system that is done intelligently by the machine, which can adjust the balance between the outside air and indoor air to reach air confort or cool. Fuzzy system is applied using Sugeno fuzzy inference using 81 rules to customize the exhaust fan and fan in the room.Keywords: Fuzzy system, Smart home, Sugeno fuzzy.